The role of liquid biopsy in early detection and monitoring of oral cancer - Devaraji, Mahalakshmi; Ravikumar, Lokeshvar (Oral oncology reports, 2024)
•High-throughput sequencing and digital PCR improve sensitivity and accuracy.•Early Detection: ctDNA can be detected before symptoms, improving early-stage diagnosis.•Monitoring: Tracks ctDNA levels to assess treatment response and detect relapse.